ERP system implementation from the ground up: The ERP5 development process and tools - de Carvalho, Rogério Atem (2009)
The design and implementation of an ERP system involves capturing the information necessary for implementing a system that supports enterprise management. This process should go down through different abstraction layers, starting on enterprise modeling and finishing at coding. For the case of Free/Open Source ERP, the lack of proper modeling methods and tools jeopardizes the advantages of source code availability. Moreover, the distributed, decentralized decision-making, and source-code driven development culture of open source communities, generally does not rely on methods for modeling the higher abstraction levels necessary for an ERP solution. The aim of this paper is to present a development process and supportive tools for the open source enterprise system ERP5, which covers the different abstraction levels involved, taking into account well established standards and practices, as well as new approaches, by supplying Enterprise, Requirements, Analysis, Design, and Implementation workflows and tools to support them. © 2010, IGI Global.